2023
DOI: 10.3390/s23094424
|View full text |Cite
|
Sign up to set email alerts
|

Low-Cost Water Quality Sensors for IoT: A Systematic Review

Abstract: In many countries, water quality monitoring is limited due to the high cost of logistics and professional equipment such as multiparametric probes. However, low-cost sensors integrated with the Internet of Things can enable real-time environmental monitoring networks, providing valuable water quality information to the public. To facilitate the widespread adoption of these sensors, it is crucial to identify which sensors can accurately measure key water quality parameters, their manufacturers, and their reliab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 99 publications
0
34
0
2
Order By: Relevance
“…It is intended to provide some details regarding the possible applications, the sensors exploited, and the characteristics of the wireless communication channel. More exhaustive reviews on such topics can be found in the literature [2,4,6,[28][29][30][31].…”
Section: Review Of Swg Based On Standard Radio Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is intended to provide some details regarding the possible applications, the sensors exploited, and the characteristics of the wireless communication channel. More exhaustive reviews on such topics can be found in the literature [2,4,6,[28][29][30][31].…”
Section: Review Of Swg Based On Standard Radio Communicationmentioning
confidence: 99%
“…Measured information include but are not limited to pressure, temperature, flow, pH, turbidity. Such quantities can be used to assess water quality [6,7], detect and locate leaks [3,8] and monitor the health state of the structure in general [9,10]. Data transfer among the nodes of the Water Sensor Network (WSN) relies on radio-based communication in the vast majority of cases.…”
Section: Introductionmentioning
confidence: 99%
“…The previous research demonstrates that EC probes possess certain qualities that make them suboptimal for MSHS deployment. Firstly, EC probes have a short life span and cannot be left in the solution indefinitely [ 24 , 28 ]. Separate measuring tanks [ 22 , 25 ] or pumping the solution through a pipe with mounted sensors [ 26 ] have been proposed but do not address the durability concerns of EC probes.…”
Section: Introductionmentioning
confidence: 99%
“…Silva, Löfkvist [ 35 ] proposed a system that pumps nutrient solution through a tube with a penetrative UV-Vis spectrometer (STS-UV-L-50-400, Ocean Insight ) set up. Using a self-learning AI model, the system was able to successfully observe changes in the N, phosphorus (P) and K. This system, using the self-learning AI model, was then used to test samples that were collected from different stages of growth from a greenhouse [ 24 ]. These samples were put through the system and their nutrient content was successfully analyzed showing that this technique could be used to manage a nutrient solution accurately.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation